Adrenal insufficiency is prevalent in HbE/β‐thalassaemia paediatric patients irrespective of their clinical severity and transfusion requirement. (13th June 2013) - Nakavachara, Pairunyar; Viprakasit, Vip
Summary: Objectives: Transfusion dependency is known to cause endocrinopathies in patients with thalassaemia such as adrenal insufficiency, because transfusion‐related iron overload is injurious to endocrine organs. Children with HbE/ß‐thalassaemia vary greatly in red cell transfusion requirement and some are transfusion dependent (TD), whereas others are nontransfusion dependent (NTD). Because iron overload is thought to be the primary cause of adrenal insufficiency, TD children with HbE/ß‐thalassaemia are considered likely candidates for the development of adrenal insufficiency, while the adrenal function of NTD children is generally considered to be normal. As yet, the prevalence of adrenal insufficiency among children with NTD HbE/β‐thalassaemia is not known. The present study was performed to (i) assess the prevalence of adrenal insufficiency in children with both TD and NTD HbE/β‐thalassaemia and to evaluate whether there is any difference in the prevalence of adrenal insufficiency between both groups and (ii) determine the type of adrenal insufficiency (primary or secondary). Methods: We investigated the prevalence of adrenal insufficiency among TD ( n  = 42) and NTD ( n  = 43) children with HbE/β‐thalassaemia by assessing morning serum cortisol levels, and we distinguished between primary and secondary adrenal insufficiency by assessing the cortisol responses following the 1‐ and 250‐μg ACTH stimulation tests. Results: The prevalence of adrenal insufficiency among TD and NTD children with HbE/β‐thalassaemia was 50% and 53·5%, respectively. By using the 250‐μg ACTH stimulation test, at least 39% and 23·5% were diagnosed with adrenal gland hypofunction in TD and NTD children, respectively. Conclusion: This is the first study to show that adrenal insufficiency is common among all children with HbE/β‐thalassaemia, irrespective of their transfusion history or requirement. Our findings have important implications for the clinical management of these children.